Empowering students' leadership skills through the R.E.A.D project - Idrus, Faizah (Penerbit UPSI, 2023)
What are youth leadership skills? How can they be nurtured? Who can help nurture these skills? What are the roles and responsibilities of teachers in nurturing Youth Leadership Skills (YLS)? These are some of the fundamental questions that are answered through the R.E.A.D Project discussed in this book. Before discussing these topics further, it is paramount to define the terms Youth, Adolescent or Adulthood and whether these terms can be used interchangeably.